Uma proposta de leitura para as tiras de Armandinho - Testa, Danilo Baptista (2021)
This work aims to propose some questions about reading comprehension of the textual genre comic strip in elementary school, based on principles of Social Semiotics and studies related to reading and textual genres. The research justifies itself because the comic strips are a textual genre to be privileged in the classroom, following the guidelines by PCN (Parâmetros Curriculares Nacionais) and BNCC (Base Nacional Comum Curricular). We also have to bring out that comic strips are appearing in school supplies and have, more recently, found in social media a support and, at the same time, guaranteed their acceptance among children, young people and adults as a creative form of communication. Bearing in mind the objective of this research, Armandinho's comic strips, produced by Alexandre Beck, were selected for analysis. In general, our work calls attention to the necessity of working comic strips reading in classroom in a perspective which brings out the reader’s role as an active subject who appeals to several strategies to produce any sense in the text